EFFECT OF MARKETING MIX AND NATIONAL CULTURE ON CONSUMER BUYING INTENTION FOR MUSIC PRODUCTS: A CASE STUDY OF INDONESIAN AND INDIAN CONSUMERS - Oswari, Teddy; Kusumawati, Reni Diah; Yusnitasari, Tristyanti; Shukla, Vijay Kumar (UI Scholars Hub, 2021)
Manuscript type: Research articles.Research Aims: To determine the effect of marketing mix and culture on consumer buying intention on music product.Design/methodology/approach: The research conducted a different test to determine there are whether or not differences in consumer behavior in Indonesia and in India.Research Findings: The results of this study can provide information to music industry about the factors that can attract consumer buying intention of music products, so the music industry can determine the right product marketing strategy.Theoretical Contribution/Originality: This research was conducted by analyzing the perceptions of consumers from Indonesia and India by paying attention to internal and external factors such as the culture of Indonesia and India.Practitioner/Policy Implication: Reducing piracy of music works, with the implementation of laws that can ensnare piracy that occurs.Research limitation/Implications: The research is only seen from consumer perceptions, while the perceptions of company or music industry are still not done.